The malleability of working memory and visuospatial skills: a randomized controlled study in older adults - Stepankova, Hana; Lukavsky, Jiri; Buschkuehl, Martin; Kopecek, Miloslav; Ripova, Daniela; Jaeggi, Susanne M (Developmental psychology, 2014)
There is accumulating evidence that training on working memory (WM) generalizes to other nontrained domains, and there are reports of transfer effects extending as far as to measures of fluid intelligence. Although there have been several demonstrations of such transfer effects in young adults and children, they have been difficult to demonstrate in older adults. In this study, we investigated the generalizing effects of an adaptive WM intervention on nontrained measures of WM and visuospatial skills. We randomly assigned healthy older adults to train on a verbal n-back task over the course of a month for either 10 or 20 sessions. Their performance change was compared with that of a control group. Our results revealed reliable group effects in nontrained standard clinical measures of WM and visuospatial skills in that both training groups outperformed the control group. We also observed a dose-response effect, that is, a positive relationship between training frequency and the gain in visuospatial skills; this finding was further confirmed by a positive correlation between training improvement and transfer. The improvements in visuospatial skills emerged even though the intervention was restricted to the verbal domain. Our work has important implications in that our data provide further evidence for plasticity of cognitive functions in old age.
Keywords: Memory, Short-Term; přenos učení (psychologie); krátkodobá paměť; Female; psychologické testy; ženské pohlaví; Aging; Space Perception; Transfer, Psychology; lidé; Psychological Tests; Male; Aged; praxe (psychologie); stárnutí; vnímání prostoru; senioři; mužské pohlaví; Practice, Psychological; Humans